Environmentally sustainable fabrication of SnO2/fly ash/biochar nanocomposite for enhanced photocatalytic performance for degradation of Ofloxacin and Rose Bengal - Khushboo Kumari; N. S. Moyon; Mohammed Ahmaruzzaman (Scientific Reports)
Abstract A ternary nanocomposite SnO2/FA/Biochar was synthesized using the sol-gel process to degrade Ofloxacin (Pharmaceutical) and Rose Bengal (RB) dye. Transmission electron microscopy, X-ray powder diffraction, Scanning electron microscopy, X-ray photoelectron spectroscopy, photoluminescence spectroscopy and UV-Vis diffuse reflectance spectroscopy were used to characterize the prepared composite’s structure, surface morphology, composition, and surface area. The SnO2/FA/Biochar nanocomposite, which was synthesized, has a particle size of 14.43 nm. The test results showed that SnO2 nanoparticles clustered together on the surface of Fly ash and Biochar. Under sun irradiation, the composite exhibited excellent photocatalytic efficacy in decomposing Rose Bengal and Ofloxacin. The maximum degradation rates of 99.12% and 88.08% were attained with catalyst doses of 0.01 g/L for RB dye and Ofloxacin, respectively, within 60 min each. The improved photocatalytic activity may be ascribed to the photocatalyst’s reduced rate of charge recombination and lowered bandgap value. The synthesized SnO2/FA/Biochar nanocomposite has a direct band gap of 2.3 eV, as determined by Tauc’s plot. The degradation of RB and Ofloxacin by exposure to light followed a reaction kinetics mechanism identified as pseudo-first-order, having rate constants of 0.0250 min− 1 and 0.0159 min− 1, respectively. The photocatalyst may be used for a maximum of five cycles while maintaining an efficiency above 75%. The impact of pH was also examined. The photodegradation activity of SnO2/FA/Biochar under visible light was investigated, resulting in efficient contamination removal from the water.